The Correlation Between Education Level, Knowledge and Motivation in Volunteer Performance: a Post-Study on Action Research in Developing Educator Volunteers for COVID-19 Based on community empowerment using a tiered and online platform in Indonesia - Khuzaiyah, Siti; Priyogo, Nur Izzah; Setianto, Gigih (Bioinformatics and Biomedical Research Journal, 2020)
Coronavirus infection is spreading globally, including in Indonesia. The coronavirus transmits so quickly; there is panic in the community to avoid transmission. Stakeholders could develop educator volunteers based on community empowerment to increase public knowledge so that they can prevent transmission of the Corona Virus. Aims. This study aimed to determine the correlation between education level, knowledge and motivation in volunteer performance after training on developing educator volunteers of covid-19. Methods. This study was action research with a post-test evaluation approach The population in this study were 250 educator volunteers of covid-19. The sampling technique used a Slovin formula with the total sample was 50 people. The data were analyzed using the Pearson chi-square test and Spearman rank. Results. There was a significant correlation between motivation for volunteer performance (p-value 0.014). Meanwhile, the education and knowledge variables did not have a substantial correlation on volunteer performance with p-value 0.917 and 0.243, respectively. Conclusions. Full support is needed for volunteers so that they are motivated to carry out their roles as educator volunteers of covid-19.